TiC particle reinforced CoNiCrW series high-entropy alloy composite material as well as preparation method and application of TiC particle reinforced CoNiCrW series high-entropy alloy composite material

Through TiC particles, the CoNiCrW-based high-entropy alloy composite is enhanced, which solves the problem of insufficient performance of high-temperature alloys in high-temperature environments, and achieves high tensile strength and wear resistance. It is suitable for the flame barrel of aero engine combustion chamber and the wear-resistant layer of turbine blades. Preparation.

CN119243015APending Publication Date: 2025-01-03AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411218096.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The performance of existing high-temperature alloys is difficult to improve in high temperature environments above 1000℃, resulting in limited safety and reliability of the flame cylinder and the wear-resistant layer of the aero engine combustion chamber, and the addition of ceramic particles leads to a sharp decline in metal plasticity. Achieve toughness matching.

Method used

TiC particles are used to enhance CoNiCrW-based high-entropy alloy composite material. By adjusting the volume ratio and particle size of TiC particles and high-entropy alloy, a (Ti, W)C compound transition layer is formed to improve the temperature resistance and compatibility of the material, and combined with Prepared by additive manufacturing process to form high-performance composite materials.

Benefits of technology

A composite material with high tensile strength and wear resistance at a temperature above 1100°C and extends the service life of the components, improving the performance of the flame cylinder of the aero engine combustion chamber and the wear-resistant layer of the turbine blade.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243015A_ABST
    Figure CN119243015A_ABST
Patent Text Reader

Abstract

The invention relates to a TiC particle reinforced CoNiCrW series high-entropy alloy composite material and a preparation method and application thereof, and belongs to the technical field of composite material manufacturing. According to the TiC particle reinforced CoNiCrW series high-entropy alloy composite material, the volume of TiC particles in the composite material ranges from 6 vol.% to 22 vol.%, and the volume of the high-entropy alloy ranges from 78 vol.% to 94 vol.%. The particle size of the TiC particles is 50-80 microns, and the particle size of the high-entropy alloy is 40-90 microns; the content of the W element in the CoNiCrW series high-entropy alloy ranges from 16.1 wt.% to 18.1 wt.%. The W element in the CoNiCrW series high-entropy alloy is quickly diffused to the surfaces of TiC particles to form a thin interface layer, so that the interface bonding force is improved, the interface cracking risk is effectively reduced, and the internal metallurgical quality of a composite material and a workpiece is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite material manufacturing technology, and in particular to a TiC particle reinforced CoNiCrW series high entropy alloy composite material and a preparation method and application thereof. Background Art

[0002] The combustion chamber flame tube and the wear-resistant layer of the turbine blade are both important components of the aircraft engine. The combustion chamber is one of the key hot end components of the aircraft engine, responsible for mixing and burning fuel and gas to generate thrust. The wear-resistant layer of the working surface of the turbine blade mostly adopts a serrated blade crown structure with a tight design. During the working process, friction is generated between them, absorbing vibration energy, thereby reducing the fuel consumption rate of the engine and improving engine performance.

[0003] Both the combustion chamber flame tube and the turbine blade wear-resistant layer need to withstand temperatures above 1000°C. Currently, both are mainly made of high-temperature alloys, such as GH3230, GH5188, etc. However, the high-temperature performance of high-temperature alloys is difficult to exceed 1000°C. As the operating temperature requirements are further increased, their performance and life are limited, which seriously restricts the safety and reliability of existing components and the improvement of overall performance.

[0004] In order to improve the temperature resistance, composite materials composed of metal and ceramic are often used. However, the biggest technical difficulty in using composite materials for the preparation of combustion chamber flame tubes is that the plasticity of the metal decreases sharply due to the addition of ceramic particles, and it is impossible to match the strength and toughness. If composite materials are used for the preparation of turbine blade wear-resistant layers, their high-temperature wear resistance and toughness need to be improved. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a composite material of TiC particle reinforced CoNiCrW series high entropy alloy and its preparation method and application, so as to obtain a composite material with good high temperature performance, matched strength and toughness, and high wear resistance.

[0006] On the one hand, the present invention provides a composite material of TiC particles reinforced CoNiCrW series high entropy alloy, wherein the volume of TiC particles in the composite material is 6vol.%~22vol.%, and the volume of high entropy alloy is 78vol.%~94vol.%; the particle size of TiC particles is 50~80 microns, and the particle size of high entropy alloy is 40~90 microns; the W element content in the CoNiCrW series high entropy alloy is 16.1wt.%~18.1wt.%.

[0007] Furthermore, the volume of TiC particles in the composite material is 6 vol.% to 16 vol.%.

[0008] Furthermore, at room temperature, the tensile strength is above 1032 MPa and the elongation is above 9.5%.

[0009] Furthermore, at 1273K, the tensile strength of the obtained composite material is above 191MPa, and the elongation is above 16.8%.

[0010] Furthermore, the volume of TiC particles in the composite material is greater than 16 vol.% to 22 vol.%.

[0011] Furthermore, at room temperature, the tensile strength of the obtained composite material is above 1105 MPa, and the hardness is above 40.1 HRC.

[0012] Furthermore, at 1273 K, the tensile strength of the obtained composite material is above 205 MPa; at 1373 K, the tensile strength of the obtained composite material is above 127 MPa.

[0013] On the other hand, the present invention provides a method for preparing a TiC particle reinforced CoNiCrW series high entropy alloy composite material, wherein TiC particles are first mixed with a CoNiCrW series high entropy alloy, and then prepared by an additive manufacturing process to obtain a CoNiCrW series high entropy alloy-based composite material.

[0014] Furthermore, the TiC particle reinforced CoNiCrW series high entropy alloy composite material is used to prepare the flame tube of the combustion chamber of an aircraft engine.

[0015] Furthermore, the TiC particle reinforced CoNiCrW series high entropy alloy composite material is used to prepare a wear-resistant layer of a turbine blade.

[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0017] 1. The present invention uses CoNiCrW series high entropy alloy as a matrix, and then adds TiC particles as a reinforcement phase. Under the cooperation of CoNiCrW series high entropy alloy and TiC particles, the obtained composite material has high temperature resistance and high performance, and can meet the use in a high temperature environment;

[0018] 2. The present invention controls the volume of TiC particles in the composite material to be 6 vol.% to 22 vol.%, and the volume of the high entropy alloy to be 78 vol.% to 94 vol.%; the particle size of the TiC particles is 50 to 80 microns, and the particle size of the high entropy alloy is 40 to 90 microns. At room temperature, its tensile strength is above 1032 MPa and its hardness is above 36.7 HRC; at 1273 K, its tensile strength is above 191 MPa; at 1373 K, its tensile strength is above 115 MPa.

[0019] 3. After the CoNiCrW series high entropy alloy and TiC particles are melted by additive manufacturing, the W element in the CoNiCrW series high entropy alloy quickly diffuses to the surface of the TiC particles and forms a thin interface layer, which can ensure the interface bonding force between the CoNiCrW series high entropy alloy matrix and the TiC particle phase, thereby improving the compatibility between the CoNiCrW series high entropy alloy and the TiC particles, effectively reducing the risk of interface cracking, and greatly improving the internal metallurgical quality of the composite material and the product.

[0020] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0022] Figure 1 This is a scanning electron microscope image of the microstructure of TiC ceramic reinforced composite materials;

[0023] Figure 2 This is a dark-field transmission electron microscope photograph of the microstructure of TiC ceramic reinforced composite materials. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0025] The combustion chamber flame tube and the turbine blade wear layer are both important components of aircraft engines, and both need to withstand temperatures above 1000°C. Currently, both are mainly made of high-temperature alloys, such as GH3230, GH5188, etc. However, the high-temperature performance of high-temperature alloys is difficult to exceed 1000°C, which seriously restricts the safety and reliability of existing components and the improvement of overall performance.

[0026] In order to improve the temperature resistance, composite materials composed of metal and ceramic are often used. However, the biggest technical difficulty in using composite materials for the preparation of combustion chamber flame tubes is that the plasticity of the metal decreases sharply due to the addition of ceramic particles, and it is impossible to match the strength and toughness. If composite materials are used for the preparation of turbine blade wear-resistant layers, their high-temperature wear resistance and toughness need to be improved.

[0027] Therefore, the present invention provides a composite material of TiC particles reinforced CoNiCrW series high entropy alloy, wherein the volume of TiC particles in the composite material is 6 vol.% to 22 vol.%, and the volume of the high entropy alloy is 78 vol.% to 94 vol.%; the particle size of the TiC particles is 50 to 80 microns, and the particle size of the high entropy alloy is 40 to 90 microns; the W element content in the CoNiCrW series high entropy alloy is 16.1 wt.% to 18.1 wt.%.

[0028] Compared with the prior art, the composite material provided by the present invention is based on a CoNiCrW series high entropy alloy as a matrix, and TiC particles are added as a reinforcement phase. Through the mutual cooperation of the two, the ratio and particle size of the two are adjusted, the TiC particles are evenly distributed in the matrix, and a (Ti, W) C compound transition layer or interface layer is formed between the TiC particles and the matrix, which improves the bonding ability of the TiC particles and the matrix. Therefore, the temperature resistance of the composite material is improved, and it can be stably used in a temperature environment above 1100°C, and the composite material has strong and toughness matching and / or high wear resistance.

[0029] The present invention takes CoNiCrW series high entropy alloy as the basic system, which can better carry TiC particles. The chemical composition of CoNiCrW series high entropy alloy includes C: 0.07-0.13%; Cr: 20.5-23.5%; Ni: 19.5-23.0%; W: 16.1-18.1%; Mn: 0.6-1.2%; La: 0.04-0.10%; B: 0.005-0.012%; Si: 0.2-0.5%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; ​​Pb<0.0005%; Cu<0.01%, and Co: balance.

[0030] Compared with the prior art, the CoNiCrW alloy provided in the present invention is a cobalt-based alloy. By changing the elements, the mixing entropy value of the alloy can be changed. The mixing entropy value exceeds 1.5R, which meets the requirements of high entropy alloys and is easier to form a solid solution, so that the matrix and the composite material have better stability at high temperatures. The CoNiCrW alloy produces a lattice distortion effect in the structure and a delayed diffusion effect in the kinetics, so that the alloy matrix is ​​strengthened and is conducive to the generation of nano-scale precipitation phases, thereby achieving the improvement of the temperature bearing capacity and mechanical properties of the composite material.

[0031] The present invention strictly controls the chemical composition ratio in the CoNiCrW alloy, especially the W element content is 16.1wt.% to 18.1wt.%. The W element has an important influence on the high temperature performance of the CoNiCrW alloy and can significantly improve the high temperature strength of the alloy.

[0032] First, there is the solid solution strengthening effect. The W element will form a stable solid solution in the alloy lattice. Even at high temperatures, it can hinder the slip and dislocation movement of the lattice, thereby improving the alloy's deformation resistance and strength; second, there is the precipitation strengthening effect. The W element helps to form a fine and uniform precipitation phase. Especially under high temperature conditions, these precipitation phases can exist stably and hinder the movement of dislocations and the slip of grains, effectively enhancing the high-temperature strength of the alloy; third, there is the grain boundary strengthening effect. The W element can change the grain boundary structure of the alloy and increase the strength of the grain boundary. The strengthened grain boundary can effectively prevent the movement of the grain boundary and the growth of the grain, maintain the microstructural stability of the alloy at high temperatures, and thus improve the high-temperature strength and performance of the alloy and composite materials.

[0033] The W element in the CoNiCrW alloy diffuses. Under the action of the additive manufacturing process, a W-containing interface layer can be formed on the surface of the TiC particles, which can improve the bonding force between the CoNiCrW alloy matrix and the TiC particles and ensure the overall performance of the composite material. However, when the W element content is below 16.1wt.%, the W element in the CoNiCrW alloy diffuses, resulting in a decrease in the W content in the matrix, thereby reducing the heat resistance or high temperature strength of the composite material; when the W element content is above 18.1wt.%, harmful phases will be generated, ultimately leading to a decrease in the overall performance of the composite material.

[0034] The other elements in the CoNiCrW high entropy alloy of the present invention have the following main functions:

[0035] Co element: Co element in this alloy is a matrix element, mainly as a solid solution strengthening element of high entropy alloy, which can enhance the strength and heat resistance of high entropy alloy. In addition, Co element can also improve the high temperature plasticity and toughness of high entropy alloy, and improve the high temperature deformation ability of high entropy alloy.

[0036] Cr element: Cr element is mainly used to improve the oxidation resistance and corrosion resistance of high entropy alloys. Chromium can form a dense oxide film layer to prevent oxygen and other corrosive media from corroding the alloy, while improving the high-temperature oxidation stability of high entropy alloys.

[0037] Ni element: Ni element can improve the plasticity and toughness of the alloy, and at the same time form a solid solution with other elements to enhance the strength and heat resistance of the high entropy alloy.

[0038] Fe element: Fe element is mainly used to adjust the organization of high entropy alloy and improve its processing performance. Iron forms a solid solution with other elements, and at the same time helps stabilize the lattice structure of high entropy alloy, and improves the strength and heat resistance of high entropy alloy.

[0039] C element: C element is usually used to form carbides to improve the hardness and wear resistance of high entropy alloys. Reasonable control of carbon content can improve the heat treatment process and mechanical properties of high entropy alloys.

[0040] Mn element: Mn element is usually used to improve the cold working performance and hot corrosion resistance of high entropy alloys. Mn element can increase the strength and hardness of high entropy alloys and improve the processing performance of alloys.

[0041] The remaining components in the CoNiCrW series high entropy alloy are all trace elements, among which La element improves the alloy's oxidation resistance and high temperature strength. B element improves the alloy's hardness and strength, and Si element enhances the alloy's oxidation resistance and fluidity. P and Cu elements can improve hardness and strength, and Ag and Bi elements can improve corrosion resistance, but the content must be strictly controlled, otherwise it will seriously affect the alloy's brittleness. S and Pb elements are impurity elements and their content must be strictly controlled.

[0042] The present invention uses CoNiCrW series high entropy alloy as matrix and adds TiC particles as reinforcement phase to prepare composite material. Through the interaction of the above elements, the matrix can be guaranteed to have stable performance, thereby ensuring the performance of the obtained composite material.

[0043] Specifically, the chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.07-0.13%; Cr: 20.5-23.5%; Ni: 19.5-23.0%; W: 16.1-18.1%; Mn: 0.6-1.2%; La: 0.04-0.10%; B: 0.005-0.012%; Si: 0.2-0.5%; Fe≤2.5%; P<0.002%; S<0.002%; Ag<0.0005%; Bi≤0.0001%; ​​Pb<0.0005%; Cu<0.01%, Co: balance.

[0044] Preferably, the chemical composition of the CoNiCrW series high entropy alloy includes, by mass percentage, C: 0.10%; Cr: 22.1%; Ni: 21.5%; W: 17.3%; Mn: 0.95%; La: 0.07%; B: 0.008%; Si: 0.35%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%, Co: balance;

[0045] Specifically, the particle size of the CoNiCrW-based high entropy alloy is 40 to 90 microns.

[0046] Specifically, the particle size of the TiC particles is 50 to 80 microns.

[0047] It should be noted that in the present invention, the CoNiCrW series high entropy alloy is spherical, and its particle size is controlled within the range of 40 to 90 microns; the TiC particles are quasi-spherical, and their particle size is controlled within the range of 50 to 80 microns.

[0048] When the particle size is within the above range, the powder particle size is more uniform. There are two main benefits to particle size control. The first is to ensure the uniformity and consistency of the additive manufacturing process, which is conducive to the stacking and melting of layers in the additive manufacturing process, and can ensure that the resulting composite material has high performance and temperature resistance; the second is to ensure the fluidity of the raw materials and the stability of the molten pool. The uniform particle size range makes the fluidity in the additive manufacturing equipment better and can be evenly stacked, thereby improving the molding quality and surface smoothness. However, when the particle size range is exceeded, it is easy to lead to a decrease in the quality of the composite material forming, resulting in uneven stacking or unstable melting quality, which reduces the dimensional accuracy and mechanical properties of the composite material.

[0049] Preferably, the particle size of the CoNiCrW-based high entropy alloy is 50 to 80 microns.

[0050] More preferably, the particle size of the CoNiCrW-based high entropy alloy is 60 to 70 microns.

[0051] Preferably, the particle size of the TiC particles is 50 to 70 microns.

[0052] More preferably, the particle size of the TiC particles is 60 to 65 microns.

[0053] It should be noted that TiC particles have good chemical stability and compatibility, and have good chemical stability and compatibility with other alloy elements at high temperatures. It can form stable compounds and phases with elements in high entropy alloys (such as Co, Ni, Cr, etc.), and is not easy to decompose or react at high temperatures, which helps to maintain the stability and performance of the composite material. In addition, TiC has good hardness and wear resistance, and can effectively protect the alloy matrix under high temperature and high stress environments, extending the service life of composite materials or parts.

[0054] In addition, the thermal conductivity and thermal expansion coefficient of TiC are similar to those of CoNiCrW high entropy alloys, which is beneficial to reduce the stress, deformation and even cracks caused by thermal expansion mismatch between the matrix and the reinforcement phase, thereby improving the stability and reliability of the composite material.

[0055] The TiC particles of the present invention cannot be replaced by carbides such as WC. Although they also have good hardness and wear resistance, WC has poor compatibility with the CoNiCrW series high entropy alloy matrix, which may cause adverse chemical reactions or interactions in the matrix, resulting in instability or performance degradation of the composite material. At the same time, the thermal expansion coefficient of WC may not match that of the high entropy alloy matrix, which may cause cracks or interface peeling problems during thermal cycles, reducing the strength of the composite material.

[0056] Specifically, the volume content of TiC particles added in the composite material is in the range of 6 vol.% to 22 vol.%.

[0057] It should be noted that the present invention uses TiC particles as a reinforcing phase and a CoNiCrW series high entropy alloy as a metal matrix. The composite material is prepared by reinforcing the CoNiCrW series high entropy alloy with TiC particles. The TiC particles and the elements in the high entropy alloy (such as Co, Ni, Cr, etc.) can form stable compounds and phases, and the obtained composite material has high temperature resistance and mechanical properties as a whole.

[0058] In the present invention, the amount of TiC particles added needs to be controlled, and the content is controlled at 6 vol.% to 22 vol.%, and the overall effect of the obtained composite material is better. When the content of TiC particles is lower than 6 vol.%, the strength of the composite material is not significantly improved due to the low content of TiC particles. When the content of TiC particles is higher than 22 vol.%, the brittleness increases rapidly due to the high ceramic content, and the composite material cannot eliminate cracks and is difficult to form. The content of TiC particles in the present invention can be 6 vol.%, 8 vol.%, 10 vol.%, 13 vol.%, 15 vol.%, 18 vol.%, 20 vol.% or 22 vol.%.

[0059] Preferably, the volume of TiC particles in the composite material is 6 vol.% to 16 vol.%.

[0060] Specifically, at room temperature, the tensile strength is above 1032 MPa and the elongation is above 9.5%.

[0061] Specifically, at 1273K, the tensile strength of the obtained composite material is above 191 MPa, and the elongation is above 16.8%.

[0062] Preferably, the volume of TiC particles in the composite material is >16 vol.% to 22 vol.%.

[0063] Specifically, at room temperature, the tensile strength of the obtained composite material is above 1105 MPa, and the hardness is above 40.1 HRC.

[0064] Specifically, at 1273 K, the tensile strength of the obtained composite material is above 205 MPa; at 1373 K, the tensile strength of the obtained composite material is above 127 MPa.

[0065] Specifically, the TiC particles are dispersed in the composite material.

[0066] It should be noted that dispersed distribution can make titanium carbide evenly distributed in the matrix material, ensuring the consistency of the composite material's performance and avoiding the situation where the performance of a local area is too low or too high. Titanium carbide dispersed in the composite material can effectively hinder the expansion of cracks, thereby enhancing the strength and toughness of the composite material and improving the overall tensile and compressive properties.

[0067] The invention provides a method for preparing a CoNiCrW series high entropy alloy-based composite material. TiC particles are firstly mixed with the CoNiCrW series high entropy alloy, and then the mixture is prepared by an additive manufacturing process to obtain the CoNiCrW series high entropy alloy-based composite material.

[0068] Compared with the prior art, the present invention weighs TiC particles and CoNiCrW series high entropy alloy according to corresponding volume ratios, then mixes the two, and then adopts an additive manufacturing process to melt and prepare a composite material.

[0069] The present invention generates a uniformly distributed fine TiC particle reinforcement phase in the composite material through an additive manufacturing process. The dispersed TiC particles have a good strengthening effect on the high-temperature strength of the composite material, and there are no defects such as micro cracks and holes inside the composite material. In addition, through the additive manufacturing process, the W element in the CoNiCrW series high entropy alloy quickly diffuses to the surface of the TiC particles and forms a thin interface layer to ensure the interface bonding force between the CoNiCrW series high entropy alloy matrix and the TiC particle phase, thereby improving the compatibility between the CoNiCrW series high entropy alloy matrix and the TiC particles, effectively reducing the risk of interface cracking, greatly improving the internal metallurgical quality of the composite material, and being able to prepare large-sized temperature-resistant parts.

[0070] Specifically, the surface of the TiC particle phase has an interface layer, and the interface layer is a tungsten-containing interface layer.

[0071] Specifically, the interface layer comprises a (Ti, W)C compound and has a thickness of 50 to 200 nm.

[0072] Preferably, the thickness of the interface layer is 50-200 nm.

[0073] It should be noted that the thickness of the interface layer is mainly affected by the particle size of the original TiC particles. In order to ensure fluidity, the particle size of the selected TiC particles is 50-80 microns, so the thickness of the interface layer is controlled at 50-200nm. The larger the particle size of the original TiC particles, the thicker the corresponding interface layer.

[0074] Specifically, the additive manufacturing is a laser selective melting process, a laser melting deposition process or an electron beam selective melting process.

[0075] When the additive manufacturing is a laser selective melting process, the power of the laser selective melting is 250-300W, the scanning speed is 1000-1100mm / s, the scanning spacing is 0.11mm, and the layer thickness is 50μm;

[0076] When the additive manufacturing is a laser melting deposition process, it includes both single-channel and dual-channel methods. The powder feeding amount of the powder feeding channel is 1600rpm-2000rpm, and the powder carrier gas flow rate is 6L / min-8L / min; the laser power is 700-800W, and the scanning speed is 600-700mm / min;

[0077] When additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5000-5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 500-600℃.

[0078] Specifically, the TiC particle reinforced CoNiCrW series high entropy alloy composite material provided by the present invention is used to prepare the wear-resistant layer of the combustion chamber flame tube and turbine blade of an aircraft engine, has a temperature resistance of more than 1000°C, and has high toughness and wear resistance.

[0079] In order to more clearly describe the present invention, the following examples and comparative examples are provided. Figure 1-2 Further explanation.

[0080] Example 1

[0081] Preparation of CoNiCrW high entropy alloy-based composite materials: comprising the following steps:

[0082] S1: CoNiCrW series high entropy alloy powder and titanium carbide ceramic powder (i.e., TiC particles) are mixed according to corresponding volume ratios, wherein the titanium carbide ceramic powder accounts for 16 vol.% of the total volume; and the CoNiCrW series high entropy alloy powder is spherical, and its particle size is controlled within the range of 60 microns; the titanium carbide ceramic powder is quasi-spherical, and its particle size is controlled within the range of 60 microns;

[0083] The chemical composition of CoNiCrW high entropy alloy is C: 0.10%; Cr: 22.1%; Ni: 21.5%; W: 17.3%; Mn: 0.95%; La: 0.07%; B: 0.008%; Si: 0.35%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0084] S2: Spread the mixed powder, and then use laser selective melting for additive manufacturing, the power of the laser selective melting is 280W, the scanning speed is 1000mm / s, the scanning interval is 0.11mm, and the layer thickness is 50μm; obtain a composite material.

[0085] Example 2

[0086] The preparation process of Example 2 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Example 2 is C: 0.07%; Cr: 20.5%; Ni: 19.5%; W: 16.1%; Mn: 0.6%; La: 0.04%; B: 0.005%; Si: 0.2%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0087] Example 3

[0088] The preparation process of Example 3 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Example 3 is C: 0.13%; Cr: 23.5%; Ni: 23.0%; W: 18.1%; Mn: 1.2%; La: 0.10%; B: 0.012%; Si: 0.5%; Fe: 2.5%; P: 0.0015%; S: 0.0018%; Ag: 0.0004%; Bi: 0.0001%; ​​Pb: 0.0004%; Cu: 0.005%; Co: balance;

[0089] Comparative Example 1

[0090] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Comparative Example 1 is W: 15.1%.

[0091] Comparative Example 2

[0092] The preparation process of Comparative Example 2 is substantially the same as that of Example 1, except that the chemical composition of the CoNiCrW high entropy alloy in Comparative Example 2 is W: 19.1%.

[0093] Comparative Example 3

[0094] The preparation process of Comparative Example 3 is substantially the same as that of Example 1, except that Comparative Example 3 is a cobalt-based high-temperature alloy GH5188, which does not contain titanium carbide particles.

[0095] Performance Testing

[0096] The above-mentioned Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, mainly including tensile strength and toughness at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 1.

[0097] Table 1 Performance test results

[0098]

[0099] It can be seen from Examples 1-3 and Comparative Examples 1-3 and Table 1 that when the composition ratio provided in Examples 1-3 of the present invention is used, by adjusting and controlling the composition ratio of the CoNiCrW series high entropy alloy, and then adding titanium carbide ceramic as a reinforcement phase, a portion of W in the CoNiCrW series high entropy alloy reacts with the titanium carbide ceramic to form a thin interface layer, which can ensure the interface bonding force between the CoNiCrW series high entropy alloy matrix and the titanium carbide ceramic phase, thereby improving the strength of the composite material, and the other part of W is preserved in the alloy substrate after material addition, thereby ensuring the high temperature resistance of the alloy substrate.

[0100] The composite material provided by the present invention has been tested for its performance. At room temperature, its tensile strength is above 1087MPa and its hardness is above 38.9HRC; at 1273K, its tensile strength is above 192MPa; at 1373K, its tensile strength is above 115MPa. The composite material obtained by the present invention has a higher tensile strength than the cobalt-based high-temperature alloy GH5188, whether at room temperature or at high temperature.

[0101] Example 4

[0102] The preparation process of Example 4 is substantially the same as that of Example 1, except that in Example 4, the titanium carbide ceramic powder accounts for 6 vol.% of the total volume.

[0103] Example 5

[0104] The preparation process of Example 5 is substantially the same as that of Example 1, except that in Example 5, the titanium carbide ceramic powder accounts for 10 vol.% of the total volume.

[0105] Example 6

[0106] The preparation process of Example 6 is substantially the same as that of Example 1, except that in Example 6, the titanium carbide ceramic powder accounts for 19 vol.% of the total volume.

[0107] Example 7

[0108] The preparation process of Example 7 is substantially the same as that of Example 1, except that in Example 7, the titanium carbide ceramic powder accounts for 22 vol.% of the total volume.

[0109] Comparative Example 4

[0110] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that in Comparative Example 4, the titanium carbide ceramic powder accounts for 25 vol.% of the total volume.

[0111] Performance Testing

[0112] The above-mentioned Examples 4-7 and Comparative Example 4 were subjected to performance tests, mainly including tensile strength and toughness at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 2.

[0113] Table 2 Performance test results

[0114]

[0115] Combining Examples 1, 4-7 and Comparative Example 4 with Table 2, it can be seen that the amount of TiC particles is closely related to the performance of the composite material. When the TiC particles account for 6 vol.% to 22 vol.% of the total volume, the performance of the composite material is better. According to the performance test, at room temperature, its tensile strength is above 1032 MPa and its hardness is above 36.7 HRC; at 1273 K, its tensile strength is above 191 MPa; at 1373 K, its tensile strength is above 121 MPa. When the TiC particles account for too high a total volume, such as 25 vol.%, the composite material will crack and cannot be used.

[0116] The present invention can control the amount of TiC particles to obtain composite materials with different properties, which can be used in different scenarios. When the TiC particles account for 6vol.% to 16vol.% of the total volume, a strong and tough matching composite material can be obtained. According to the performance test, at room temperature, its tensile strength is above 1032MPa and its elongation is above 9.5%; at 1273K, its tensile strength is above 191MPa and its elongation is above 16.8%; at 1373K, its tensile strength is above 121MPa and its elongation is above 41.6%. The obtained TiC particle reinforced CoNiCrW high entropy alloy composite material can be used to prepare the flame tube of the combustion chamber of an aircraft engine.

[0117] When TiC particles account for 16 vol.% to 22 vol.% of the total volume, a composite material with high wear resistance can be obtained. According to the performance test, at room temperature, its tensile strength is above 1105 MPa and its hardness is above 40.1 HRC; at 1273 K, its tensile strength is above 205 MPa; at 1373 K, its tensile strength is above 127 MPa. The obtained TiC particle reinforced CoNiCrW high entropy alloy composite material can be used to prepare the wear-resistant layer of turbine blades.

[0118] Example 8

[0119] The preparation process of Example 8 is substantially the same as that of Example 1, except that in Example 8, the particle size of the CoNiCrW high entropy alloy powder is controlled at 80 microns; and the particle size of the TiC particles is controlled at 40 microns.

[0120] Example 9

[0121] The preparation process of Example 9 is substantially the same as that of Example 1, except that in Example 9, the particle size of the CoNiCrW-based high entropy alloy powder is controlled at 40 microns; and the particle size of the TiC particles is controlled at 90 microns.

[0122] Comparative Example 5

[0123] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that in Comparative Example 5, the particle size of the CoNiCrW high entropy alloy powder is controlled at 30 microns; and the particle size of the TiC particles is controlled at 100 microns.

[0124] Comparative Example 6

[0125] The preparation process of Comparative Example 6 is substantially the same as that of Example 1, except that in Comparative Example 6, the particle size of the CoNiCrW high entropy alloy powder is controlled at 30 microns; and the particle size of the TiC particles is controlled at 100 microns.

[0126] Performance Testing

[0127] The above-mentioned Examples 8-9 and Comparative Examples 5-6 were subjected to performance tests, mainly including tensile strength and toughness at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 3.

[0128] Table 3 Performance test results

[0129]

[0130] Combining Examples 1, 8-9 and Comparative Examples 5-6 with Table 3, it can be seen that the present invention adds TiC particles to the CoNiCrW high entropy alloy, controls the particle size of the TiC particles to be 50-80 microns, and the particle size of the high entropy alloy to be 40-90 microns. Within the above range, the resulting composite material has higher performance. According to the performance test, at room temperature, its tensile strength is above 1068MPa and its hardness is above 39.4HRC; at 1273K, its tensile strength is above 192MPa; at 1373K, its tensile strength is above 119MPa.

[0131] Examples 10-14, Comparative Examples 7-8

[0132] Example 10

[0133] The preparation process of Example 10 is substantially the same as that of Example 1, except that in Example 10, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 250 W, the scanning speed is 1000 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.

[0134] Embodiment 11

[0135] The preparation process of Example 11 is substantially the same as that of Example 1, except that in Example 11, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 300 W, the scanning speed is 1100 mm / s, the scanning interval is 0.11 mm, and the layer thickness is 50 μm.

[0136] Example 12

[0137] The preparation process of Example 12 is substantially the same as that of Example 1, except that a single-channel powder feeding method is adopted in Example 12, and the mixed powder of CoNiCrW high entropy alloy and TiC is respectively loaded into a powder feeding channel, the powder feeding amount of the powder feeding channel is 2000rpm, and the powder carrier gas flow rate is 7L / min; the power of laser melting deposition is 700W, and the scanning speed is 600mm / min.

[0138] Embodiment 13

[0139] The preparation process of Example 13 is substantially the same as that of Example 1, except that in Example 13, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5000W, the thickness of each powder layer is 50μm, and the preheating temperature is 500℃.

[0140] Embodiment 14

[0141] The preparation process of Example 14 is substantially the same as that of Example 1, except that in Example 14, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 5500W, the thickness of each powder layer is 50μm, and the preheating temperature is 600℃.

[0142] Comparative Example 7

[0143] The preparation process of Comparative Example 7 is substantially the same as that of Example 1, except that in Comparative Example 7, laser selective melting is used for additive manufacturing, the power of the laser selective melting is 350 W, the scanning speed is 1500 mm / s, the scanning spacing is 0.11 mm, and the layer thickness is 50 μm.

[0144] Comparative Example 8

[0145] The preparation process of Comparative Example 8 is substantially the same as that of Example 1, except that in Comparative Example 8, when the additive manufacturing is an electron beam selective melting process, the vacuum degree is 2×10 -3 ±0.5×10 -4 mbar, the working voltage is 60kV, the electron beam power is set to 6500W, the thickness of each powder layer is 50μm, and the preheating temperature is 750℃.

[0146] Performance Testing

[0147] The above-mentioned Examples 10-14 and Comparative Examples 7-8 were subjected to performance tests, mainly including tensile strength and toughness at room temperature, high temperature 1273K and 1373K. The test results are shown in Table 4.

[0148] Table 4 Performance test results

[0149]

[0150] It can be seen from Examples 1, 10-14 and Comparative Examples 7-8 and Table 4 that when the method for preparing the composite material provided by the embodiment of the present invention is adopted, the obtained composite material has high tensile strength and toughness. After performance testing, the hardness at room temperature is above 39.7HRC; at 1273K, the tensile strength is above 209MPa, and at 1373K, the tensile strength is above 120MPa.

[0151] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A composite material of TiC particles reinforced CoNiCrW high entropy alloy, characterized in that: The volume of TiC particles in the composite material is 6 vol.% to 22 vol.%, and the volume of the high entropy alloy is 78 vol.% to 94 vol.%; the particle size of the TiC particles is 50 to 80 microns, and the particle size of the high entropy alloy is 40 to 90 microns; the W element content in the CoNiCrW series high entropy alloy is 16.1 wt.% to 18.1 wt.%.

2. The composite material of TiC particles reinforced CoNiCrW high entropy alloy according to claim 1, characterized in that: The volume of TiC particles in the composite material is 6 vol.% to 16 vol.%.

3. The composite material of TiC particles reinforced CoNiCrW high entropy alloy according to claim 2, characterized in that: At room temperature, the tensile strength is above 1032MPa and the elongation is above 9.5%.

4. The composite material of TiC particles reinforced CoNiCrW high entropy alloy according to claim 2, characterized in that: At 1273K, the tensile strength of the obtained composite material is above 191MPa and the elongation is above 16.8%.

5. The composite material of TiC particles reinforced CoNiCrW high entropy alloy according to claim 1, characterized in that: The volume of TiC particles in the composite material is greater than 16 vol.% to 22 vol.%.

6. The composite material of TiC particles reinforced CoNiCrW high entropy alloy according to claim 5, characterized in that: At room temperature, the tensile strength of the obtained composite material is above 1105 MPa and the hardness is above 40.1 HRC.

7. The composite material of TiC particles reinforced CoNiCrW high entropy alloy according to claim 5, characterized in that: At 1273K, the tensile strength of the obtained composite material is above 205MPa; at 1373K, the tensile strength of the obtained composite material is above 127MPa.

8. A method for preparing the TiC particle reinforced CoNiCrW high entropy alloy composite material according to any one of claims 1 to 7, characterized in that: TiC particles are first mixed with CoNiCrW series high entropy alloy, and then prepared by additive manufacturing process to obtain CoNiCrW series high entropy alloy-based composite materials.

9. A composite material of TiC particles reinforced CoNiCrW high entropy alloy as claimed in any one of claims 2 to 4, used for preparing a flame tube of an aircraft engine combustion chamber.

10. A composite material of TiC particles reinforced CoNiCrW high entropy alloy as claimed in any one of claims 5 to 7 for use in preparing a wear-resistant layer of a turbine blade.

Citation Information

Patent Citations

  • Method for preparing TiC reinforced iron-based high-entropy alloy composite material through electric arc melting

    CN111057960A

  • Composite material taking carbide ceramic as reinforcing phase and preparation method thereof

    CN119114939A

  • CoNiCrW series high-entropy alloy-based composite material as well as preparation method and application thereof

    CN119120995A